STANDAR PENDIDIK DAN TENAGA KEPENDIDIKAN PADA JENJANG SMP - Wahyuni, Sri; Rati, Ni Wayan; Krisnawati , Ni Putu; Uma Suputra, Nyoman Wiparwa; Pisesa, Gede Ardi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The quality of education is heavily reliant on the standards of educators and education personnel (SPTK) as a key pillar in achieving National Education Standards. Objective: This study aims to provide a comprehensive analysis of the fulfillment of SPTK at the junior high school level, specifically within the context of the Merdeka Curriculum implementation. Method: Operating a qualitative approach with a descriptive-analytical case study design, data were collected at SMPN 5 Denpasar through participatory observation and in-depth interviews with the Vice Principal of Student Affairs and teaching personnel. Secondary data were sourced from educational regulations and reputable scientific literatures. Findings: The results indicate that the school has generally met the government's standards. Out of 47 teachers, 41 hold a Bachelor's degree (S1) and 6 hold a Master's degree (S2) in linear study fields, demonstrating strong pedagogical and professional competencies. Furthermore, the principal showcases proficient managerial and supervisory skills, complemented by a professional school administration team (TAS). However, a significant challenge remains regarding the service ratio of Guidance and Counseling (BK) teachers, where each BK teacher is responsible for 150 students. Conclusion: While the implementation of SPTK at SMPN 5 Denpasar is highly commendable, structured career development, adaptive technology literacy for 21st-century learning, and continuous workload evaluation are recommended to sustain educational quality.